THE EFFECT OF STRAIN HARDENING AND ANNEALING TO HARDNESS AND MICROSTRUCTURE OF COPPER - Ida Farida; Arief Rahmana (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The cold rolling process is to provide a plastic deformation to the metal by passing it between the high-pressure rollers to reduce the thickness of the metal (reduction) which will make the metal having a strain hardening phenomenon. Strain hardening effects that occur after having cold rolling can be eliminated by annealing process. To demonstrate the relationship of properties and structure of the material, cold-rolling research is carried out using copper plates. Copper specimens are made into 5 samples. Where the samples consist of annealing process treatment and rolling process. The result of the process of rolling and annealing treatment indicates that with the increase of strain in the copper after having the process of cold rolling, the higher also the value of the hardness of the copper. With the treatment of annealing process causes a decrease in copper hardness. As for the micro structure produced in the sample given the rolling process is showing the a flat and elongated grain, and for the sample without the treatment of rolling process indicates the shape of equaxial grain.